“Equity” in genomic health policies: a review of policies in the international arena - Basnayake Ralalage, Prabhathi; Mitchell, Tala; Zammit, Claire; Baynam, Gareth; Kowal, Emma; Masey, Libby; McGaughran, Julie; Boughtwood, Tiffany; Jenkins, Misty; Pratt, Gregory; Ferdinand, Angeline (Frontiers in Public Health, 2024)
IntroductionThe field of genomics is rapidly evolving and has made significant impact on the diagnosis and understanding of rare and genetic diseases, in guiding precision medicine in cancer treatment, and in providing personalized risk assessment for disease development and treatment responses. However, according to the literature, there is widespread socio economic and racial inequities in the diagnosis, treatment, and in the use of genomic medicine services. This policy review sets out to explore the concept of equity in access to genomic care, the level of inclusion of equity and how it is addressed and what mechanisms are in place to achieve equity in genomic care in the international health policy.MethodsA systematic search for genomic policies was conducted using 3 databases. In addition, General and Specific Policy Repositories, Global Consortia in Genomic Medicine, WHO Collaborating Centers in Genomics, Australian Genomics, Public Policy Projects, Global Genomic Medicine Consortium (G2MC), G2MC conference Oct 2023 and National Human Genome Research Institute databases were searched using the inclusion and exclusion criteria. Seventeen policies were selected and analyzed using the EquiFrame.ResultsThe Core Concept of access is highly cited in most of the selected policies. The CCs that are covered to a lesser degree are participation, quality, coordination of services, cultural responsiveness and non-discrimination. The CCs of liberty and entitlement are not addressed in any of the selected policies. The coverage of vulnerable communities in the policies varies from country to country.DiscussionGenomic health science is rapidly evolving and presents a major challenge for policies to remain current and effectively address new discoveries in the field. There is a relative dearth of policies that focus on clinical genetic services which may reflect a gap in policy and policy research translation and implementation. Recommendations for countries, irrespective of their economic and social contexts, include conducting regular policy reviews to accommodate the advances in genomics field and inclusion of specific mechanisms to achieve equity in genomic health. Insights and experiences in achieving healthcare equity in HICs and LMICs can offer valuable lessons for each other.